Context matters: Problematizing the policy‐practice interface in the enactment of gender equality action plans in universities. Issue 2 (19th December 2020) - Ní Laoire, Caitríona; Linehan, Carol; Archibong, Uduak; Picardi, Ilenia; Udén, Maria
Abstract: This study argues for recognition of the constitutive role of context in shaping the dynamics of the policy‐practice interface in the field of gender equality in universities. Using a comparative and reflective case‐study approach, we draw on our experiences, as action‐researchers, of developing and implementing Gender Equality Action Plans (GEAPs) in four universities in four different European countries and we explore the role of national and local context in the mediation and translation of the GEAP model. Drawing on the concepts of gendered organizations, dialogic organizational change, and policy mobilities, we argue for the need to be critical of approaches to gender equality in higher education (HE) that presume policy measures and good practice models transfer unproblematically to different HE organizations in different international contexts; instead, we draw attention to the contingent ways in which uneven gender relations articulate and manifest in different contexts, shaping possibilities for, and obstacles to, gender equality intervention. Thus, we argue that context plays a crucial constitutive role in the interpretation, enactment, and impact of gender equality policy in HE.